Perception of Oneself as a Teacher from the Perspective of Individuals Retraining for the New Profession - Joanna Łukasik (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: The purpose of this article is to identify and describe the self-perceptions of those retraining and preparing for the teaching profession. THE RESEARCH PROBLEM AND METHODS: The research problem was formulated as follows: how do postgraduate students who are retraining to become teachers perceive themselves as future teachers? Data were obtained from postgraduate students who wrote essays on Why did I choose to study teacher training and what kind of teacher would I like to be? The method of qualitative text analysis was used to analyze the essays, which were treated as secondary data. THE PROCESS OF ARGUMENTATION: The first part of the article focuses on the importance of positive self-image and self-concept in motivation for development, as they strengthen self-esteem, and translate it into attitudes and inner containment. In the empirical section, based on Leary's concept, three main categories were identified. RESEARCH RESULTS: The analysis shows that the respondents' project of themselves in the professional role of a teacher is declarative only. The categories and qualities that the respondents mentioned refer both to their negative (by contrast) and positive school experiences. Positive self-perception through the characteristics described, experiences of working in other professions and passions all motivate positive work on oneself and are a condition for becoming a teacher. CONCLUSION, INNOVATIONS, RECOMMENDATIONS: In the final conclusions, a proposal was made for a new way of recruiting and temporary qualification for the teaching profession. Attention was paid to strengthening intrinsic motivation to work on one's development as a prerequisite for preparing for work and becoming a teacher.